Optimization Studies on Improving the Dielectric Properties of Alkali Treated Fibers from Phaseolus Vulgaris Reinforced Polyester Composites by Central Composite Design. Issue 11 (2nd November 2021) - Gurukarthik Babu, B.; Princewinston, D.; Padmanaban, V.C.; Lathief Sherief, G.Abdul; Kiruba Sankar, M.; Aravind Bhaskar, P.V.
ABSTRACT: This study investigates the dielectric efficiency of a composite prepared using a fiber extracted from Phaseolus vulgaris . The extraction of fiber was statistically modeled using face-centered central composite design. The concentration of NaOH and extraction time was taken as the process variables and dielectric strength was taken as the response. The numerically optimized model for the extraction of fiber from Phaseolus vulgaris of alkali treatment showed 14.325 kV/cm as dielectric strength of initial NaOH concentration of 3% and time period of 51 min. The model was significant with R 2 = 0.9323 and adjusted R 2 = 0.884. The linear, quadratic & interactive relationship between the response (dielectric strength) and variables (NaOH & time) was also established. This study explains the importance of NaOH and time period in establishing the fiber extraction by the alkali treatment process.